1997
DOI: 10.1159/000174116
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril and Pressure-Diuresis in Hypertensive Rats Transgenic for Mouse Renin Gene

Abstract: The recent development of a transgenic rat strain bearing the mouse ren-2 renin gene [TGR(mRen2)27] has provided a new monogenetic model of hypertension. Other hypertensive rat strains are characterized by a blunted pressure-diuresis-natriuresis response such that higher renal perfusion pressures are required to excrete normal amounts of water and sodium. Dysfunction of the renin-angiotensin and nitric oxide systems may cause in this abnormality. This study examined the effect of enalapril on the pressure-natr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…In addition, it has been demonstrated that EETs play an important role in the regulation of the afferent arteriole autoregulatory responses to changes in perfusion pressure by limiting pressure‐mediated vasoconstriction . It was therefore conceivable to assume that net intrarenal deficiency of EETs in TGR contributes to the well‐known impairment of the pressure–natriuresis relationship and, in accordance with the concept originally proposed by Guyton et al . and supported by findings from several other groups, this impairment is the critical mechanism responsible for the pathophysiology of hypertension.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, it has been demonstrated that EETs play an important role in the regulation of the afferent arteriole autoregulatory responses to changes in perfusion pressure by limiting pressure‐mediated vasoconstriction . It was therefore conceivable to assume that net intrarenal deficiency of EETs in TGR contributes to the well‐known impairment of the pressure–natriuresis relationship and, in accordance with the concept originally proposed by Guyton et al . and supported by findings from several other groups, this impairment is the critical mechanism responsible for the pathophysiology of hypertension.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, it has been shown that chronic pharmacological blockade of sEH in these models results in an antihypertensive action that is associated with increased intrarenal availability of EETs, as well as improvements in renal haemodynamic autoregulatory efficiency and the pressure–natriuresis relationship . Because TGR reveal a well‐documented impairment of the autoregulation of renal haemodynamic and pressure–natriuresis relationship, and in view of our recent finding that TGR exhibit reduced tissue availability of EETs, we hypothesized that inhibition of sEH may result in an antihypertensive action that is mediated by an increase in EET bioavailability, with consequent improvement of both renal haemodynamic autoregulation and the impaired pressure–natriuresis relationship.…”
Section: Introductionmentioning
confidence: 97%
“…It is also well established that the renin-angiotensin system (RAS) can modulate the slope of the pressure-natriuresis mechanism and, when activated, it can lead to a marked suppression of the pressure-natriuresis relationship [17][18][19]. Despite our knowledge, so far it has not been demonstrated that impairment of the pressure-natriuresis mechanism really precedes the development of ANG IIdependent forms of hypertension; all available studies [7][8][9][11][12][13][14][15] have revealed a blunted pressure-natriuresis relationship in ANG II-dependent forms of hypertension only in rats that already exhibited a hypertensive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that the slope of the pressure-natriuresis relationship can be substantially influenced by alterations in the basal levels of angiotensin II (ANG II) and it has been shown that ANG II-dependent models of hypertension exhibit a suppression of the pressure-natriuresis relationship that is implicated to play a role in the pathophysiology of hypertension in these models [7][8][9][10][11][12][13][14][15][16][17][18]. According to the hypothesis proposed by Guyton et al [19], the impairment of the pressure-natriuresis mechanism should precede the development of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Solhaug et al (1996a) suggested that NO is vital in the developing kidney to maintain normal physiological function and to protect the immature kidney during pathophysiological stress. Springate et al (1997) noted that mouse renin genetransgenic rats had a blunted pressure-diuresis-natriuresis response that was corrected by inhibition of the renin-ANG system and suggested that their production of NO was normal. It was suggested that the infusion of L-arginine caused diuresis and natriuresis, possibly via the formation of NO in the rat kidney and that endogenous ANG II was not involved in the L-arginine-induced renal actions (Urabe et al, 1996).…”
Section: Other Vasculaturesmentioning
confidence: 99%